Preliminary Assessment of the Soil Foundation Characteristics Utilizing the 2D Resistivity Imaging and Down-Hole Seismic Refraction Techniques: A Case Study in Tenth of Ramadan City, Egypt - Soliman, Shokry A.; Shebl, Salah; El Khafif, Ahmed; hazley, T.F. S; Farag , M.H. (Iraqi Journal of Science, 2021)
Two-dimensional electrical resistivity imaging and seismic refraction, in the form of down-hole survey, were applied to delineate the subsurface section and elastic moduli and identify geotechnical characteristics of subsurface materials in the 10th of Ramadan industrial area, Cairo, Egypt. The results of four 2-D profiles of electrical resistivity, in the form of dipole–dipole and Wenner configurations, revealed that the subsurface section contains two main geo-electrical layers; the first is made of sand, some silt, and gravels, reflecting low resistivity values ranging from 25 to 65.5 ohm m. This layer is overlying a high resistivity layer (65.5 to135 ohm m), corresponding to medium to coarse sand, with gravel and calcareous materials. It is worth noting that that the down-hole technique was used to measure velocities of P and S waves in order to derive the low strain dynamic elastic properties, such as Poisson’s ratio, Shear modulus, stress ratio, concentration index, N-value, and the ultimate and allowable bearing capacities of the subsurface soil, down to an approximate depth of 30 m in the borehole at the site. In addition, the Vs30 value was calculated and revealed that the soil is categorized as a NEHRP class (D). Furthermore, the results of geotechnical parameters and elastic moduli were found to be realistic and sensible for the purposes of engineering constructions and imply that the soil in the study area is characterized by fairly to moderately competent quality. A new empirical correlation is proposed between the obtained Vs and resistivity values, where Vs = 1.0302 ρ + 172.74.